The origins of Christendom in the West - Kreider, Alan, 1941- (T&T Clark, 2001)
For well over a millennium the civilization of Western Europe was 'Christendom, ' with Christianity the dominant religion, buttressed by social and legal structures. This volume studies Christendom at its origins, bringing the insights of leading scholars in the fields of ancient history, theology, patristics, and liturgy to bear on aspects of Europe's Christianization. From a missiological perspective, the contributors ask what is Christianity's impact upon culture, what is culture's impact upon Christianity? Focusing on the first four centuries, but also looking forward to the future of Chris.